The Effect of Sub-MIC of Salvadora persica on Growth and Virulence Gene Expressions in Streptococcus mutans: Effect of S. persica on Virulence Gene Expressions in S. mutans - Jamal, Ali I.; Jalal Balaky, Salah T. (Cellular and Molecular Biology, 2023)
Dental caries is a multifactorial infectious chronic disease caused by particular bacteria and their virulence products that causes demineralization and progressive deterioration of the dental enamel. Many studies have proven miswak to have a critical antibacterial impact, particularly on cariogenic bacteria and periodontal pathogens, in the oral cavity. This study aimed to investigate the effect of different concentrations of Salvadora persica plant extract on growth and virulence gene expressions at mRNA levels in S. mutans. A total of 191 clinical samples from tooth swabs were collected, and sub-cultured on specific medium agar identified using biochemical and molecular approaches. MIC for the extract was determined and a bacterial growth curve was made to determine the growth phases and the optimum time for adding the extract at different concentrations. RT-qPCR technique was performed, and the REST-2009 software program was used for data analysis. Out of 191 swabs from the tooth 31 isolates were identified using several biochemical and molecular tests. Several S. mutans biofilm-related virulence genes and their Ct values were produced from RT-PCR under the effect of low and high doses of Meswak concentrations. Ct values and reaction efficiency were produced in RT-qPCR by Rotorgen3000, data then were analysed by REST-2009 software. Five isolates were selected to examine the effect of the extract on the mRNA levels using qPCR after growing them with both doses of the extract for about 30hrs. Levels of virulence gene mRNA were regulated differentially in cultures with added both extract doses. The isolates produced significantly lower virulence gene mRNA levels in cultures grown with both plant extract doses. The results produced in this study here provide new insights regarding several virulence gene expressions in S. mutans at the molecular levels when grown under different concentrations of Salvadora persica plant extract.